Preservation of socket for immediate dental implants in aesthetic zone from upper jaw : aesthetic approach-case repor = Preservación del alvéolo para implantes dentales inmediatos en zona estética del maxilar superior : enfoque estético-reporte de caso - Colorado Zuluaga, Juliana
Ensuring optimal aesthetic outcomes in dental implant cases within the maxillary anterior area requires careful consideration of socket preservation and atraumatic tooth extraction. These factors play a crucial role in achieving successful and aesthetically pleasing treatments. The objective of this study is to present a series of clinical cases involving dental extractions of anterior maxillary teeth with a poor prognosis. This study highlights the importance of socket preservation and atraumatic tooth extraction in ensuring optimal aesthetic results in dental implant cases within the maxillary anterior area. In these cases, a two-armed lever technique was planned for atraumatic alveolar preservation during the extraction process.Following the tooth extraction, the fresh socket was reclassified, and dental implants were subsequently placed using a modified drilling technique in certain cases. The authors assessed the primary stability of the implants, while in other cases, bone regeneration procedures were performed. The presented clinical cases demonstrate the successful implementation of the two-armed lever technique for atraumatic alveolar preservation, leading to favorable outcomes in terms of primary implant stability and bone preservation. Techniques for bone preservation after tooth extraction aim to minimize post-extraction bone resorption. By implementing appropriate protocols, such as the concept of the dual zone and the two-armed lever technique, successful outcomes can be achieved in terms of both aesthetics and preservation of the alveolar bone.